RASASUNDARI DEBI: THE FIRST WOMAN AUTO-BIOGRAPHER OF 19TH CENTURY BENGAL (International Journal of Food and Nutritional Sciences, 2022)
Rasasundari Debi is among the earliest woman writer in Bengali literature. Her autobiography ‘Amar Jiban’is known as the first woman autobiography in Bengali literature. She lived in such a time when education was unimaginable for woman and a literate woman was synonymous with a cursed woman. But she refused to remain illiterate an constructed an identity independent of her husband and children. She was born to a rural zamindari family in the small village of Potajia, in Pabna in 1809. She was raised by her widowed mother, with whom she developed an emotional attachment. She was known to the alphabet at an early age. At the age of twelve she was married and from then she spent a life like in a cage. She always felt the grief of being separated from her mother. She was very much conscious about the society where none wish to educate the girl child. As she was a religious person, her desire to be able to read ‘Chaitanya Bhagabat’made her dream come true. She taught herself to write later on. She wrote the autobiography at the age of 59, where she wrote about different social issues.